Ekphrasis Tulisan Emosi dalam Memahami Regulasi Emosi - Santoso, Agus (Jurusan Bimbingan dan Konseling Islam, 2019)
Each individual has a unique verbal and visual interaction that can be referred to as ekphrasis. Ekphrasis is a picture of the self that results from the process of self-expression as evidenced by the use of words. The process of cognition and emotional activity of a person like this can be used as an alternative in expressing emotions through writing. A development concept based on metatheory and dialectical studies in therapeutic interventions, between Cognitive Behavioral Therapy (CBT) and Dialectic Behavioral Therapy (DBT). This strategy seeks to strike a balance between self-acceptance and a change strategy. This conception has led to an Ekphrasis Tulisan Emosi (ETE) technique that refers to an alternative in regulating emotions, namely; suppression and cognitive reappraisal. Suppression is a management strategy by storing or holding expressions of emotions. Reappraisal cognitive is the use of the mind to replace certain emotions. Internal processes that occur in a person will be easily expressed by linking emotional regulation skills with writing activities.